Effect of working capital efficiency, liquidity, and solvency on the profitability of automotive industry companies and their components listed on the Indonesian stock exchange in 2004-2008 - Isthi Pinasthika (Institute of Accounting Research and Novation (IARN), 2022)
This study aims to determine the effect of working capital efficiency, liquidity and solvency on company profitability in food and beverage companies listed on the Indonesia Stock Exchange. The research design is casual associative research. The research population is all food and beverage companies listed on the Indonesia Stock Exchange in the 2004-2008 period. The sampling technique used was purposive sampling. The population data for the study were 15 companies and a sample of 14 companies was obtained. The independent variables in this study are working capital efficiency, liquidity and solvency. The dependent variable in this study is company profitability. The data analysis method used is correlation, regression, determination, t test and F test with a significant level of 0.05. Based on the results of the analysis using multiple correlation tests on the relationship between working capital efficiency, liquidity and solvency on company profitability with an R square value of 0.433, this shows a fairly strong influence. The multiple linear regression equation in this study is formulated as Y = -80.823 + 3.259 WCT + 12.988 CR - 0.013 DER + e, working capital turnover and currentratio has a positive effect and the depth to equity ratio has a negative effect with constant assumptions. Regression analysis produces an adjusted R² of 0.406 or 40.6%